Risk of Enteric Infection in Patients with Gastric Acid Supressive Drugs: A Population-Based Case-Control Study - Chia-Jung Kuo (MDPI AG, 2021)
Long-term use of gastric-acid-suppressive drugs is known to be associated with several adverse effects. However, the association between enteric infection and acid suppression therapy is still uncertain. This study aimed to evaluate the association between gastric acid suppression and the risk of enteric infection. Materials and Methods: We conducted a population-based case-control study using the data from Chang Gung Research Database (CGRD) in Taiwan. Between January 2008 and December 2017, a total of 154,590 adult inpatients (age > 18) were identified. A pool of potential eligible controls according to four propensity scores matching by sex, age, and index year were extracted (n = 89,925). Subjects with missing data or who received less than 7 days of proton pump inhibitors (PPIs) and/or H2-receptor antagonists (H2RAs) were excluded. Finally, 17,186 cases and 69,708 corresponding controls were selected for analysis. The use of PPIs and H2RAs, the result of microbiological samples, and co-morbidity conditions have been analyzed. Confounders were controlled by conditional logistic regression. Results: 32.84% of patients in the case group used PPIs, compared with 7.48% in the control group. Of patients in the case group, 9.9% used H2RAs, compared with 6.9% in the control group. Of patients in the case group, 8.3% used a combination of PPIs and H2RAs, compared with 2.7% in the control group. The most common etiological pathogens were Enterococcus (44.8%), Clostridioides difficile (34.5%), and Salmonella spp. (10.2%). The adjusted odds ratio (OR) for PPI use with enteric infection was 5.526 (95% confidence interval [CI], 5.274–5.791). For H2RAs, the adjusted odds ratio was 1.339 (95% confidence interval [CI], 1.261–1.424). Compared to the control group, persons with enteric infection had more frequent acid-suppressive agent usage. Conclusions: This study demonstrates that gastric-acid-suppressive drug use is associated with an increased risk of enteric infection after adjusting for potential biases and confounders.